Accountability in national courts for international crimes against children - Lubaale, Emma Charlene (Acta criminologica, 2018)
Children are principle targets in situations of armed conflict, crimes against humanity and genocide. The atrocities committed against them in these contexts fall in the category of international crimes and can be prosecuted either by international criminal courts or national courts. The Rome Statute of the International Criminal Court (Rome Statute) has laudable provisions geared towards ensuring accountability for crimes committed against children. Thus, when prosecutions take place in the International Criminal Court (ICC), the best interest of child-victims is to a large extent catered for. It is pertinent to note, however, that the ICC operates on the principle of complementarity; it only admits cases when national courts are unwilling or unable to prosecute. This means that the bulk of international crimes committed against children are prosecuted by national courts, and consequently the success of international criminal justice for children depends more on what national courts can deliver as opposed to what the ICC can deliver. Sudan, Kenya and Uganda are notable states where international crimes against children have been pervasive. Using these states as case studies, this article illustrates that there is an impunity gap insofar as accountability for international crimes against children is concerned because procedural and substantive laws of these states are not sensitive to the special needs of child-victims and, they were not written for the specific purpose of prosecuting international crimes against children. The article concludes that national legal reform must remain on the international agenda if international crimes against children are to be effectively accounted for.